Analysis of publishing activity on human resource management systems of enterprises in the bases of electronic resources in terms of influence over its innovative receptivity - Dyuzhev, V. G.; Boichenko, O. I.; Bolshakov, D. (Ljubljana School of Business, Slovenia, 2019)
This article is dedicated to research of the electronic resources of the world and Ukrainian university libraries in the area of Human Resource Management Systems (HRMS) for purposes of identifying trends, regularities and forming complex measures regarding their efficiency improvement. In the course of research the analysis of indicators of publishing activity performance was made. Increment rate indicators were calculated. Growth trends of HRMS publications in the world and Ukrainian scientific libraries were determined.
Keywords: electronic resources; Human Resource Management Systems; Ukrainian scientific libraries